Influence of Soil Exchangeable Cations on Growth, Nutrient Uptake and Physiology of Oil Palm Seedlings - Murdi, Ahmad Afandi (2007)
Increasing the efficiency of nutrient uptake can significantly reduce the cost of production, since fertilizer cost is about 30% of total cost of oil palm production. Despite many agronomic trials on the response of oil palm to various fertilizers, there were few published information on the multidisciplinary study of physiological responses with cations e.g. potassium (K), calcium (Ca) and magnesium (Mg). Therefore, this study is necessary to increase efficiency in the oil palm nutrient management system through multidisciplinary aspects of soil and plant physiology. The trial was conducted in the nursery of the Malaysian Palm Oil Board (MPOB) Research Station in Lahad Datu, Sabah. Oil palm seedlings were grown in polybag filled with two types of soil i.e Semporna Family which contain high exchangeable Ca or Lumpongan Family with low exchangeable Ca. Semporna soil was tested at 32 levels of K and Mg and Lumpongan was tested at 33 levels of K, Ca and Mg with three replicates. Among the parameters studied were vegetative measurements, relative chlorophyll content and leaf relative water content. Destructive samplings of whole plants were done and seedlings were separated into rachis, pinnae, stem and roots. The tissues were then used to determine K, Mg and Ca concentrations and uptake. Soil samples were taken at the beginning and the end of trials and subsequently analysed for cations content. Leaf gas exchange parameters were measured using a portable infrared gas analyser two weeks before the final destructive sampling. Pre-treatment analysis showed that the exchangeable K, Mg and Ca in Lumpongan soil were 0.35, 6.74 and 6.07 cmol (+) kg-1 respectively. Meanwhile, in Semporna soil the exchangeable K, Mg and Ca were 0.17, 1.22 and 33.50 cmol (+) kg-1. Application of cation fertilizers significantly increased respective exchangeable cations in both soils. There were non significant increases in seedling dry matter components with regards of cations treatments in both soils. The concentration and uptake of K in seedling components were increased significantly by K fertilizer in both soils. Magnesium fertilizer was not recommended on Lumpongan soil but 6.69 g of Mg per seedling are needed to sustain the growth of seedling in Semporna soil. The seedling recovery efficiency for K and Ca in Lumpongan soil was about 3.65 and 1.21%, respectively. Meanwhile, in Semporna soil the recovery efficiency for K and Mg was about 4.56 and 2.54%, respectively. This study showed that total cation in oil palm seedling leaves was largely determined by soil exchangeable calcium rather than K or Mg. The proportion of individual tissue cation to total cations was fairly constant, i.e about 29% if the soil exchangeable calcium is high (> 25 cmol (+) kg-1). This was considered sufficiently balance for oil palm nutrient requirement. However, excessive amount of exchangeable Mg in soil (> 4.75 cmol (+) kg-1) such as Lumpongan soil resulted in an imbalance proportion of individual tissue cation to total cation. The oil palm seedling vegetative growth, leaf tissues turgidity and chlorophyll content exhibited less sensitivity to cation treatments as indicated by non significant difference in both soils. Excessive amount of Ca in Semporna soil contributed to low shoot to root ratio of the seedlings by 7 to 9% as compared to Lumpongan soil. The photosynthesis rate on Lumpongan and Semporna soils ranged from 8.52 to 9.45 μmol m-2s-1 and 7.07 to 8.66 μmol m-2s-1, respectively. This implies that, cations treatments did not significantly reduce the photosynthesis rate. It was also concluded that the stomata conductance and intercellular CO2 concentrations of seedlings in both soils were adequate to support leaf gas exchange as indicated by non significant different between treatments. In conclusion, combinations of K1 (35.11 g K) + Mg0 (0 g Mg) + Ca1 (14 g Ca) and K2 (70.22 g K) + Mg1 (6.69 g Mg) were recommended for sustaining optimum growth, nutrient uptake and physiological requirement in oil palm seedlings grown in Lumpongan and Semporna soils, respectively. These combinations take into account the total dry matter production, uptake, recovery efficiency and physiological characteristics of oil palm seedlings at each cation levels.